MODEL PENGELOLAAN TERBAIK UNTUK KEBERLANJUTAN DAERAH ALIRAN SUNGAI (DAS) PADA SUB DAS CILIWUNG HULU (The Best Management Model For Sustainability Watershed At The Upper Ciliwung Sub Watershed) - Mahawan Karuniasa; Haqqi Annazili Daulay; Muchammad Saparis Soedarjanto (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTThe sustainability of the ecosystem functions of the Upper Ciliwung Sub Watershed is disrupted, indicated by the exceeding of the minimum erosion hazard level compared to its tolerable erosion. This condition is caused by imbalance between forest areas compared to other land uses such as dryland agricultural, paddy fields, and settlement of the watershed. The purpose of this study was to determine the best watershed management practices in the Upper Ciliwung Sub Watershed based on the watershed sustainability model. The data for the sustainability model were obtained through the Analytical Hierarchy Process (AHP). The results showed that the area of forest had the highest value among other land cover aspects with a value of 52.8%. In succession, the next priority was the area of paddy fields by 24.4%; the area of dryland agriculture was 17.9% and the settlement area was 4.9%. It can be concluded that efforts were needed to: 1). Increase the area of forests and reduce the area of dryland agriculture; 2). Managing the area of settlements; 3). Increasing the area of paddy fields.Keywords: watersheds, management practices, environmental restoration ABSTRAKKeberlanjutan fungsi ekosistem Sub DAS Ciliwung Hulu terganggu, ditunjukkan oleh nilai tingkat bahaya erosi minimum yang melebihi batas yang dapat ditoleransi. Hal ini karena kawasan hutan memiliki proporsi yang tidak sebanding dengan luas pertanian lahan kering, luas sawah dan luas permukiman di wilayah tersebut. Tujuan dari penelitian ini adalah untuk menentukan praktik pengelolaan DAS terbaik di Sub DAS Ciliwung Hulu berdasarkan model keberlanjutan DAS. Data yang digunakan untuk keberlanjutan DAS Ciliwung Hulu diperoleh melalui Analytical Hierarchy Process (AHP). Hasil penelitian menunjukkan bahwa luas hutan memiliki nilai tertinggi di antara aspek tutupan lahan lainnya dengan nilai 52,8%. Secara berturut-turut, prioritas berikutnya adalah luas sawah sebesar 24,4%; luas pertanian lahan kering dengan nilai 17,9% dan luas permukiman sebesar 4,9%. Dapat disimpulkan bahwa diperlukan upaya untuk: 1). Meningkatkan luas hutan dan mengurangi luas pertanian lahan kering; 2). Mengelola luas permukiman; dan 3). Meningkatkan luas sawah.Kata kunci: Daerah Aliran Sungai, praktik manajemen, restorasi lingkungan